Iklim Komunikasi Organisasi dalam Proses Pembelajaran Pesantren (Studi Kasus pada Pesantren Al – Hilal 3 Gegerkalong Kecamatan Sukasari) - Yosa Fitriani; Ike Junita Triwardhani (UNISBA Press, 2024)
Abstract. Communication climate is important because it links the organizational context with the concepts, feelings and hopes of organizational members. Islamic boarding schools as educational institutions that form and develop moral values ​​are the driving force and inspiration in creating national morality. Through teaching, discussion and daily practice, students are given a deep understanding of religious values. This research aims to determine and explain the characteristics of the organizational communication climate in the learning process at the Al – Hilal 3 Islamic Boarding School, Sukasari District, Bandung. By identifying problems in depth regarding the characteristics of the organizational communication climate. This research uses a qualitative method with a case study approach. The paradigm used is the constructivism paradigm. Researchers sought in-depth information through observations and interviews with several parties, namely boarding school leaders and teachers/caregivers at the Al – Hilal 3 Islamic boarding school, Sukasari District, Bandung. The results of this research can be concluded that the organizational communication climate at the Al-Hilal 3 Gegerkalong Islamic Boarding School is based on six dimensions. Support, trust, decision making, honesty, openness and high performance goals. This research also shows how communication plays a role in building an organizational communication climate in the learning process at Al-Hilal 3 Islamic Boarding School. In this research, internal and external factors were also found in the organizational climate at Al-Hilal 3 Gegerkalong Islamic Boarding School. Abstrak. Iklim komunikasi penting karena mengaitkan konteks organisasi dengan konsep-konsep, perasaan-perasaan dan harapan-harapan anggota organisasi. Pesantren sebagai lembaga pendidikan yang membentuk dan mengembangkan nilai-nilai moral merupakan penggerak dan pemberi inspirasi dalam menciptakan moralitas bangsa. Melalui pengajaran, diskusi, dan praktek sehari-hari, santri diberikan pemahaman mendalam tentang nilai-nilai keagamaan. Penelitian ini bertujuan untuk mengetahui dan menjelaskan karakteristik iklim komunikasi organisasi dalam proses pembelajaran di Pesantren Al – Hilal 3 Kecamatan Sukasari Bandung. Dengan mengidentifikasi masalah secara mendalam tentang karakteristik iklim komunikasi organisasi. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Paradigma yang dipakai adalah paradigma konstruktivisme. Peneliti mencari informasi mendalam malalui observasi dan wawancara beberapa pihak, yaitu Pimpinan pondok dan Pengajar/Pengasuh yang ada di pesantren Al – Hilal 3 Kecamatan Sukasari Bandung. Hasil penelitian ini dapat disimpulkan bahwa iklim komunikasi organisasi di Pondok Pesantren Al-Hilal 3 Gegerkalong berdasarkan enam dimensi. Dukungan, kepercayaan, pengambilan keputusan, kejujuran, keterbukaan, dan tujuan kinerja tinggi. Penelitian ini juga menunjukkan bagaimana komunikasi berperan dalam membangun iklim komunikasi organisasi dalam proses pembelajaran di Pesantren Al-Hilal 3. Dalam penelitian ini juga ditemukan faktor internal dan faktor eksternal pada iklim organisasi di Pesantren Al-Hilal 3 Gegerkalong.